(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The increasing incidences of microbial resistance to a wide range of antimicrobial agents are raising a great concern worldwide. The extensive use of anti¬biotics has contributed to escalate antimicrobial resistance incidences. In this regard, development of a novel compounds with the potential to fight against the ever-growing number of antimicrobial-resistant pathogenic microorganisms is need of the hour. In this study, we have synthesized Gold and Copper nanoparticles from the extracts of a wild mushroom and their activity against a broad range of bacteria is evaluated.